Design and Analysis of Various Material Two -Wheeler Engine Cooling Fins - Renjith Nimal, R.J. Golden; Rajalakshmi, A. (International Journal of Psychosocial Rehabilitation, 2019)
In order to conserve natural resources and economize energy, weight reduction has been the main focus of automobile manufacturers in the present scenario. Weight reduction can be achieved primarily by the introduction of better materials, design optimization, and better manufacturing processes. The suspension cooling fins are one of the potential items for weight reduction in automobiles, as they account for 10%–20% of the unsprung weight. This provides the vehicle with more fuel efficiency and improved riding qualities. The introduction of metal alloys made it possible to reduce the weight of cooling fins without any reduction in load-carrying capacity or stiffness. Since the aluminium alloy has more elastic strain energy storage capacity and a high strength-to-weight ratio as compared with those of steel, it can be used as the cooling fin for automobiles. Modelling and analysis of the aluminium alloy cooling fins will be done in this project